'I, Robot?' Or how transgender subjects are dehumanised - O'Shea, Saoirse Caitlin (Culture and organization, 2020)
In this essay, I focus on the earlier works of Judith Butler to discuss her understanding of gender theory and moreover do so in relation to people who are transgender. Transgender folk are important to Butler's early work but I contend that her allegorical use of them does not do justice to their precarious lives. I relate my discussion to existing work in organisational studies concerned both with Butler and trans folk and argue that Butler's concept of performativity should be (re)read alongside her other concerns with embodiment and universality to argue that, at least in relation to transgender folk, her work needs to be extended to consider issues of dysphoria in order to explain why some gender identities are refused and made abject.